Characteristics of Desirable Labor Force in Five Major Industries in Roi Et Province During the COVID-19 Pandemic - Jamalee, Nongyao; Phiriyawanthana, Wanlob (Suan Dusit Graduate School Academic Journal, 2023)
This research was qualitative research. The objectives were 1) to study the characteristics of labor force in 5 main industries in Roi Et Province 2) to study the desirable labor demand in 5 major industries in Roi Et Province. The key informants were divided into 2 groups, the first group was 9 experts involved in the selection of employees to work, and the second group consisted of 8 employees, totaling 17 people. The interview form was used to collect data. The quality check of the interview form was conducted by thesis advisor and the data analysis was based on inductive analysis method by which the data was compiled and classified systematically and then used to interpret the relationship and create a conclusion. The results showed that the characteristics of the workforce had 1) High responsibility 2) Good adaptability to different situations 3) Creativity 4) Good communication 5) Passion for work and desire to succeed. For the desirable labor demands in the 5 main industries in Roi Et Province, the professional knowledge aspect required labor forces who were knowledgeable and worked according to their preferences and aptitudes that were appropriate for the body of knowledge. For the professional skill aspect, workforce skills were required to respond to advances in technology. For the professional values aspect, pride in the profession was required. For the personality traits, labor forces were required to perform with honesty, confidentiality in their work, responsibility and good attitude. Regarding the motivation aspect, labor forces were required to have a relationship with colleagues, pride in the work and satisfaction with salary, wages and welfare rights.